More of a Receiver Than a Giver: Why Do People Unfollow in Twitter? - Kwak, Haewoon; Moon, Sue; Lee, Wonjae (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
We propose a logistic regression model taking into account two analytically different sets of factors–structure and action. The factors include individual, dyadic, and triadic properties between ego and alter whose tie breakup is under consideration. From the fitted model using a large-scale data, we discover 5 structural and 7 actional variables to have significant explanatory power for unfollow. One unique finding from our quantitative analysis is that people appreciate receiving acknowledgements from others even in virtually unilateral communication relationships and are less likely to unfollow them: people are more of a receiver than a giver.